Leader-member exchange, job satisfaction, employee engagement, and employee performance - S Suharnomo; Dian Kartika (Diponegoro International Journal of Business, 2018)
The main purpose of this paper is to investigate the effect of leader-member exchange (LMX) on employee performance. We also examine the effect of LMX on job satisfication then job satisfacton on employee performance. Furthermore, our research also test the effect of LMX on employee engagement then employee engagement on employee performance. The results of the analysis using SEM toward 105 respondents who work in Hotel B in Tegal, Indonesia, show supports for almost proposed prediction. However, our prediction that LMX have positive effect on employee performance was not supported.